2022
DOI: 10.48550/arxiv.2205.04293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do You Think You Can Hold Me? The Real Challenge of Problem-Space Evasion Attacks

Abstract: Android malware is a spreading disease in the virtual world. Anti-virus and detection systems continuously undergo patches and updates to defend against these threats. Most of the latest approaches in malware detection use Machine Learning (ML). Against the robustifying effort of detection systems, raise the evasion attacks, where an adversary changes its targeted samples so that they are misclassified as benign. This paper considers two kinds of evasion attacks: feature-space and problem-space. Feature-space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Second, exploring problem-space attacks is vital to test the realistic assumptions of feature-space evasion attacks. For example, Berger et al [36] showed that feature-space attacks in the Android domain do not serve as proxies for problem-space evasion attacks. In other words, feature-space attacks do not depict reality accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Second, exploring problem-space attacks is vital to test the realistic assumptions of feature-space evasion attacks. For example, Berger et al [36] showed that feature-space attacks in the Android domain do not serve as proxies for problem-space evasion attacks. In other words, feature-space attacks do not depict reality accurately.…”
Section: Introductionmentioning
confidence: 99%